Phytophthora Related Diseases - Megan M. Dewdney; Jamie D. Yates (EDIS)
PP262, a 2-page illustrated identification sheet by Megan Dewdney and Jamie D. Yates, can be used to identify four Phytophthora-related diseases of citrus–phytophthora foot rot, brown rot, phytopththora root rot, and diaprepes root weevil. Published by the UF Department of Plant Pathology, March 2009.